2019
DOI: 10.1021/acs.nanolett.9b03881
|View full text |Cite
|
Sign up to set email alerts
|

Toward Realistic Amorphous Topological Insulators

Abstract: The topological properties of materials are, until now, associated with the features of their crystalline structure, although translational symmetry is not an explicit requirement of the topological phases. Recent studies of hopping models on random lattices have demonstrated that amorphous model systems show a non-trivial topology. Using ab initio calculations we show that two-dimensional amorphous materials can also display topological insulator properties. More specifically, we present a realistic state-of-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 56 publications
8
46
0
1
Order By: Relevance
“…, where, for the SH conductivity, X η ¼ ŝη and for the OH conductivity (OHC), X η ¼ lη ; ŝη and l η represent the η components of the spin and of the atomic angular momentum operators, respectively. This is implemented in the PAOFLOW code [41] that has been successfully used to study topological materials [42,43] and time dependent spin dynamics [44] among other topics. For our conductivity calculations, we have increased the sampling to 200 × 200 × 1 k points in the 2D BZ.…”
mentioning
confidence: 99%
“…, where, for the SH conductivity, X η ¼ ŝη and for the OH conductivity (OHC), X η ¼ lη ; ŝη and l η represent the η components of the spin and of the atomic angular momentum operators, respectively. This is implemented in the PAOFLOW code [41] that has been successfully used to study topological materials [42,43] and time dependent spin dynamics [44] among other topics. For our conductivity calculations, we have increased the sampling to 200 × 200 × 1 k points in the 2D BZ.…”
mentioning
confidence: 99%
“…These results agree well with those obtained above from the generic TB model. Here, we did not consider the structural relaxation of the defected systems since the surface-supported film can largely hold the bulk geometry in the presence of defects, and a recent study has shown that the TI phase can persist even in amorphous state with local atomic displacements without "bulk" defects [51].…”
mentioning
confidence: 99%
“…This well-developed understanding dates back at least to studies of integer quantum Hall transitions (8)(9)(10). More recently, several classes of amorphous models have been shown to host integer quantum Hall (or Chern insulator) phases, as well as other topological states (7,(11)(12)(13)(14)(15)(16)(17)(18)(19), including numerical work that suggests differences compared to known quantum Hall transitions (19,20). Although the corresponding topological phase diagrams can be computed numerically, by simulating responses to external fields (18) or through real space topological markers (7,11), these methods are not generalizable to every discrete symmetry in every dimensionality.…”
mentioning
confidence: 99%